2020
DOI: 10.1002/marc.202000558
|View full text |Cite
|
Sign up to set email alerts
|

Multiarm Star‐Crosslinked Hydrogel: Polymer Network with Thermoresponsive Free‐End Chains Densely Connected to Crosslinking Points

Abstract: Soft tissue in biological system is a hydrogel with elaborate structure exhibiting repeatable dynamic function. In order to approach such sophisticated system, precise construction of a designed network with multi‐components is desired. This communication presents a novel hydrogel having highly dense stimuli‐responsive free‐end chains around crosslinking structure. A key molecule is a core‐crosslinked star‐shaped polymer with multiple thermoresponsive arms, which can be prepared by reversible addition–fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In addition to the aforementioned advantages, star polymers offer the possibility of incorporating a much higher number of functional groups. This has implications in a wide variety of applications, ranging from thermoplastic elastomers, [ 24 ] polyelectrolytes, [ 25 ] polyionic liquids, [ 26 ] hydrogels, [ 27 ] wearable electronics, [ 28 ] and drug carriers. [ 29 ] One can construct topologically complex architectures by controlling a number of factors to alter their dimensions, morphologies, stability, and material properties, some of which will be touched upon in this review.…”
Section: Emerging Potential Of Branched Star Polymers As Nanocarriersmentioning
confidence: 99%
“…In addition to the aforementioned advantages, star polymers offer the possibility of incorporating a much higher number of functional groups. This has implications in a wide variety of applications, ranging from thermoplastic elastomers, [ 24 ] polyelectrolytes, [ 25 ] polyionic liquids, [ 26 ] hydrogels, [ 27 ] wearable electronics, [ 28 ] and drug carriers. [ 29 ] One can construct topologically complex architectures by controlling a number of factors to alter their dimensions, morphologies, stability, and material properties, some of which will be touched upon in this review.…”
Section: Emerging Potential Of Branched Star Polymers As Nanocarriersmentioning
confidence: 99%
“…[19][20][21][22][23] Typical examples utilize phase separation of a thermoresponsive polymer such as PNIPAAm, which induces mechanical toughening above the transition temperature, and the incorporation of PNIPAAm chains as a free-end chain and microgel structure is effective. [24][25][26][27][28][29][30] Such topological control of thermoresponsive chains in a network would expand the applicability of the designed hydrogels, for example, if high dimensional stability and high clarity at the transition are imparted for a gel material.…”
Section: Introductionmentioning
confidence: 99%
“…If we can construct a crosslinked network with the smallest polymer unit for which the structure is controlled at the molecular level, we may be able to explain macroscopic changes in polymer gels with respect to the behavior of polymer chains. 17,[20][21][22][23][24][25] In previous studies, we reported that star-shaped polymers obtained from living radical polymerization, which enables precise syntheses of polymers, can be combined under conditions appropriate for obtaining polymer gels with more homogeneous network structures than polymer networks obtained by conventional free radical polymerization. [26][27][28] Using living radical polymerization, star-shaped polymers consisting of block copolymers as well as random copolymers consisting of multiple monomers can be synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…If we can construct a crosslinked network with the smallest polymer unit for which the structure is controlled at the molecular level, we may be able to explain macroscopic changes in polymer gels with respect to the behavior of polymer chains. 17,20–25…”
Section: Introductionmentioning
confidence: 99%